INFORMATION PROCESSING SYSTEM AND CONTROL METHOD FOR THE SAME - KAWANISHI EIJI (2018)
PROBLEM TO BE SOLVED: To enable the number of times of communication between a compound machine and a host computer to be reduced.SOLUTION: An information processing system 1 comprises a compound machine 2 and a host computer 3. The compound machine 2 has a compound machine control section which adds an encryption common key obtained by encrypting a common key by a public key in a public key encryption system to encryption reading information obtained by encrypting reading information by a common key in a common key encryption system, transmits the encryption reading information added with the encryption common key to the host computer 3, and can decrypt the encryption common key by a secret key. The host computer 3 includes: a host interface section acquiring the encryption reading information added with the encryption common key, requesting decryption of the encryption common key to the compound machine 2 and acquiring the common key; and a host control section decrypting the encryption reading information by the acquired common key and acquiring the reading information.SELECTED DRAWING: Figure 1 【課題】複合機とホストコンピューターとの間の通信回数を低減できるようにすることを目的とする。【解決手段】情報処理システム１は、複合機２と、ホストコンピューター３と、を備える。複合機２は、共通鍵暗号方式における共通鍵により読取情報を暗号化した暗号化読取情報に、共通鍵を、公開鍵暗号方式における公開鍵で暗号化した暗号化共通鍵を付加して、ホストコンピューター３に送信すると共に、暗号化共通鍵を秘密鍵で復号可能な複合機制御部を有する。ホストコンピューター３は、暗号化共通鍵が付加された暗号化読取情報を取得し、複合機２へ暗号化共通鍵の復号を要求して共通鍵を取得するホストインターフェース部と、取得した共通鍵により暗号化読取情報を復号して読取情報を取得するホスト制御部と、を有する。【選択図】図１